IMPACT ASSESSMENT OF AGRICULTURAL TRANSFORMATION PROJECT ON PRODUCTIVITY AND POVERTY AMONG RICE FARMERS IN KANO STATE, NIGERIA. - Balogun, O. S.; Damisa, M. A.; Yusuf, O.; Balogun, O. L. (FUDMA JOURNAL OF SCIENCES, 2020)
The study was carried out to examine the effect of agricultural transformation on the beneficiary’s productivity and poverty of rice farmers in Kano State Nigeria. A multi-stage sampling method was employed to select 571 respondents for the study. Data were collected through structured questionnaires on respondent’s income, input and output quantities as well as their expenditures. Data were analysis using descriptive statistics, Foster-Greer-Thorbecke (FGT), Propensity score matching and LATE model. Results from the study shows that respondents productivity revealed a significant difference of about 127 kg/ha in rice productivity between participants and non-participants. Also, the LATE estimates revealed an average treatment effect ATE0 of about 222.98kg/ha. Furthermore, the project had a significant effect N11, 321.4 on the participant’s consumption expenditure than the non-participants N9980.60. Moreover, participants were, able to increase their household total expenditures by N34780 per annum. Fluctuations of input/output prices insect pests and inadequate extension visits were all the major constraints faced by the farmers. It was recommended that farmers’ information and sensitization system should be overhauled and improved. Also, attention should be given to well organize extension visits for the farmers from stake holders